The combined effect of dipotassium hydrogen phosphate and paper mill sludge ash towards formation of efflorescence and properties of fly ash geopolymer mortar - Norbaizurah, Rahman (2018)
The use of aluminosilicate source with high amount of CaO has been widely used in geopolymer due to its high compressive strength at early age. The presence of Ca2+ is able to accelerate the geopolymerization process, hence produces large amount of geopolymer matrices. Nevertheless, excessive amount of Ca2+ in geopolymer also contribute to the rapid setting time and low workability. Short setting time and low workability will obstruct the process of transporting, casting and compacting, which might cause the structural disintegration due to its porous and honeycomb structure. In conventional Portland cement mixture, phosphate based admixtures have been extensively studied to retard the setting time of cement paste, yet it is scarcely studied for the use in geopolymer system. Despite of the extension on the setting time of geopolymer paste, the excessive use of this admixture may result in the formation of efflorescence that would damage the integrity of hardened geopolymer. Therefore this study was proposed to investigate the effect of secondary source material i.e. paper mill sludge ash (PMSA) and various curing temperature (30°C, 60°C and 90°C), on the properties of geopolymer mortar containing dipotassium hydrogen phosphate (K2HPO4) particularly on its role to minimize the formation of efflorescence in hardened geopolymer specimen. A series of tests were conducted to determine the rheological, mechanical and microstructural properties of geopolymer containing K2HPO4 at various percentages of 0.1%, 0.2%, 0.3%, 0.4% and 0.5% (by weight of fly ash) and PMSA. To determine the rheological properties, setting time, workability, viscosity and surface tension test were conducted while degree of reaction, compressive strength and porosity test were done to determine the mechanical properties. The leaching of alkali metal was determined using Inductively Coupled Plasma Mass Spectrometry (ICPMS) and pH test. Meanwhile, Fourier Transform Infrared Spectroscopy (FTIR) testing was conducted to identify chemical bonds and Thermogravimetric analysis (TGA) was done to determine geopolymerization products. Energy Dispersion X-Ray (EDX) and Scanning Electron Microscopy (SEM) test were conducted to investigate the microstructure and elemental composition that contributes to the strength performance of fly ash based geopolymer. Based on the experimental results, it shows that the optimum percentages inclusion of PMSA in geopolymer was 5%. The combination of 0.5% K2HPO4 with 5% PMSA has significantly prolonged the setting time, higher in compressive strength, reduce the porosity and produce denser microstructure. Higher curing temperature has accelerated the geopolymerization process and enhances the formation of geopolymer gel in geopolymer framework. In addition, it also shows the positive effect on reducing the formation of efflorescence at the surface of hardened geopolymer and lowers the pH value of leaching. Addition of CaO in geopolymer matrix has formed secondary product which is CSH gel as Ca-O bond is more susceptible to break the bonds than Al-O and Si-O. Free Ca2+ would bond with Si to form CSH gel. Based on the statistical analysis Si and Ca had “potentially important” effect while Na, Al, Fe and Mg had “possibly important” effect towards the structural disintegration of geopolymer. Each type of alkali cation and anion had its own effects on every stage of geopolymerization process. They played the vital role in the production of final structure by controlling the geopolymer gel and crystal growth hence contribute to the structural development by forming alumino-silicate structures. Therefore, the use of industrial waste (paper mill sludge ash) combined with elevated temperature curing would lead to the sustainable green construction materials that would help to preserve environment quality and natural resources.